CRITICAL DISCOURSE ANALYSIS ON SCIENTIFIC LANGUAGE IN SKINCARE PRODUCT NAMES AND DESCRIPTION - Cahyani, Ida (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines how “scientific” language in skincare product names constructs authority, efficacy claims, and consumer subject positions. Using Fairclough’s Critical Discourse Analysis (CDA), it analyzes two skincare products namely Skintific and Wardah. The analysis follows three dimensions: (1) text analysis which includes phrase analysis on lexical borrowing from science, quantification and statistical authority and hybridization of science and beauty rhetoric; (2) discursive practice which analyze how names are produced (brand style and platform constraints), distributed (packaging, e-commerce), and consumed (consumer readings of numbers and technical terms); and (3) social practice to reveal the ideology behind the text. Findings indicate systematic patterns on the scientific language is less about empirical precision and more about constructing trust and authority. The study contributes an operational scheme for identifying “scientific language” in naming, clarifies meaning-making mechanisms, and discusses implications for consumer literacy and marketing communication regulation..